On strongly faintly M-θ-i-continuous functions in Bi-Supra Topological Space - Taha H. Jasim; Reem O. Rasheed (Tikrit Journal of Pure Science, 2023)
In this paper we introduces a new definition , called i- open and via this definition we  introduce class of topological concepts(µ-θ-i-open set, µ-θ-i-closed, strong faintly µ-θ-continuity,  strong µ-θ-continuity )and we generalized these concepts in bi -supra topological space .At last  many  important theorems in strongly faintly M-θ-i-continuous functions are investigated. And study  the relationships among  these functions and other forms are discussed.